2014
DOI: 10.1152/ajplung.00083.2014
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in pulmonary macrophages mediates lung inflammatory injury via NLRP3 inflammasome activation during mechanical ventilation

Abstract: in pulmonary macrophages mediates lung inflammatory injury via NLRP3 inflammasome activation during mechanical ventilation. Am J Physiol Lung Cell Mol Physiol 307: L173-L185, 2014. First published May 16, 2014 doi:10.1152/ajplung.00083.2014.-The inflammatory response is a primary mechanism in the pathogenesis of ventilator-induced lung injury. Autophagy is an essential, homeostatic process by which cells break down their own components. We explored the role of autophagy in the mechanisms of mechanical ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…It is recognized that NLRP3 inflammasome activation in AM mediates lung inflammatory responses during MV (13). The role of autophagy in ALI, including VILI, has been controversial with some studies suggesting a protective and others a detrimental role of autophagy (17,18). In this study we found that autophagy in myeloid cells plays a protective role in the experimental LPS/MV-induced "two-hit" ALI model.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is recognized that NLRP3 inflammasome activation in AM mediates lung inflammatory responses during MV (13). The role of autophagy in ALI, including VILI, has been controversial with some studies suggesting a protective and others a detrimental role of autophagy (17,18). In this study we found that autophagy in myeloid cells plays a protective role in the experimental LPS/MV-induced "two-hit" ALI model.…”
Section: Discussionmentioning
confidence: 54%
“…Autophagy is a highly conserved, fundamental intracellular system associated with cellular homeostasis, recycling, and elimination of defective organelles, and intracellular pathogens (14,15). The role of autophagy in the mechanism of ALI has been controversial with studies that have suggested both protective and detrimental effects of autophagy (14,(16)(17)(18). On the other hand, numerous studies have demonstrated in various settings that autophagy plays an inhibitory role in secretion of IL-1β through downregulation of the NLRP3 activation (15).…”
Section: Introductionmentioning
confidence: 99%
“…Rescue of dysfunctional autophagy has been shown to play a protective role against hyperinflammatory responses from cystic fibrosis cells39, while autophagy deficiency in alveolar macrophages resulted in greater silica-induced inflammation40. In contrast, inhibition of autophagy in lung macrophages abolished mechanical ventilation-induced nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome activation and lung inflammatory injury41. In avian influenza A-infected lung epithelial cells, blocking autophagy not only reduced the cell death4243, but also decreased the production of proinflammatory cytokines43.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies have revealed the response to be inflammasome-mediated, where the stretch injury causes NLR-containing pyrin domain 3 (NLRP3) activation and induces the release of IL-1β from alveolar macrophages (4244). Additional studies showed alveolar macrophage high-mobility group box-1 (HMGB1) and possibly transient receptor potential vanilloid 4 (TRPV4) to be involved in neutrophil recruitment to the alveolar space and lung vascular permeability and lung edema (4547).…”
Section: Ventilator-induced Lung Injurymentioning
confidence: 99%